Regulation of Halal Product Certification in the Dynamics of Indonesian Legal Politics - Warsis Mawardi; Muchammad Ichsan (Justicia Islamica, 2023)
This study aimed to explore how the regulation of halal product certification in the dynamics of Indonesian legal politics, especially since the institutionalization of the halal certification system in 1975, then continued with the issuance of Law No. 8 of 1999 concerning Consumer Protection (UUPK), which transformed with the establishment of Law no. 33 of 2014 concerning Guarantee of Halal Products (UU JPH). By using a doctrinal research typology and qualitative data analysis, this research produces the following conclusions: First, the regulation of halal certification presents a political configuration, especially during the discussion of the JPH Law, resulting in pros and cons between the MUI, the government including the faction of the DPR faction regarding the institution authorized to carry out the certification, including whether or not business actors must carry out certification. Second, the shift in authority for halal certification, which was initially carried out by the MUI, after the arrival of the JPH Law, the transition and implementation of halal certification by BPJPH have triggered a political configuration that needs to be harmonized and consolidated immediately so as not to cause institutional disharmony